УПРАВЛІННЯ ІНВЕСТИЦІЯМИ В ЕНЕРГЕТИЧНУ ГАЛУЗЬ (International Journal of Innovative Technologies in Economy, 2018)
The article is devoted development of conceptual bases of establishment of conformities to law of investment development of energy of region, prognostication of investment processes, related to it, optimum management by them with the purpose of exposure of component factors of influence on this process. A research object is processes of investing of regional economy and its efficiency in the Western region. The article of research is economic conformities to law of investment development of energy of region.